MyD88: At the heart of inflammatory signaling and cardiovascular disease. (December 2021) - Bayer, Abraham L.; Alcaide, Pilar
Abstract: Cardiovascular disease is a leading cause of death worldwide and is associated with systemic inflammation. In depth study of the cell-specific signaling mechanisms mediating the inflammatory response is vital to improving anti-inflammatory therapies that reduce mortality and morbidity. Cellular damage in the cardiovascular system results in the release of damage associated molecular patterns (DAMPs), also known as "alarmins, " which activate myeloid cells through the adaptor protein myeloid differentiation primary response 88 (MyD88). MyD88 is broadly expressed in most cell types of the immune and cardiovascular systems, and its role often differs in a cardiovascular disease context and cell specific manner. Herein we review what is known about MyD88 in the setting of a variety of cardiovascular diseases, discussing cell specific functions and the relative contributions of MyD88-dependent vs. independent alarmin triggered inflammatory signaling. The widespread involvement of these pathways in cardiovascular disease, and their largely unexplored complexity, sets the stage for future in depth mechanistic studies that may place MyD88 in both immune and non-immune cell types as an attractive target for therapeutic intervention in cardiovascular disease.